Alternatives to antibiotics in diets of weaned piglets - Soraia Viana Ferreira (Ciência Rural, 2017)
This experiment was conducted to evaluate the effect of growth promoter additives an alternative to antibiotics on performance,intestinal morphology and on microbiota of 21-to-35-day-old piglets. A total of 160 commercial crossbred piglets (males and females) withinitial weight of 6.10±0.709kg were allotted in a completely randomized design with five treatments: Basal diet - Negative Control (NC); Basaldiet + antibiotic (PC); Basal diet + mannanoligosaccharides (MOS); Basal diet + organic acids (OA), Basal diet + mannanoligosacharides+ organic acids (MOS+OA), eight replicates and four piglets per experimental unit. The inclusion of additives in the diets had no effect(P>0.05) on the final average weight of piglets. Similarly, no effects (P<0.05) were observed on average daily feed intake and on average dailyweight gain. The feed conversion improved (P<0.01) with the inclusion of additives in the diets compared to piglets fed with the NC. Therewas no effect (P>0.05) of the dietary additives on intestinal morphology and microbiota composition (enterobacteria and lactobacilli). Use ofantibiotics, prebiotics, organic acids or prebiotics associated with organic acids in the diet improves feed conversion of piglets from 21 to 35days of age. The additives have no major effects on piglets’ intestinal morphology and microbiota.